Improvements in balance reaction impairments following reactive balance training in individuals with sub-acute stroke: A prospective cohort study with historical control. Issue 4 (18th May 2020) - Schinkel-Ivy, Alison; Huntley, Andrew H.; Danells, Cynthia J.; Inness, Elizabeth L.; Mansfield, Avril
ABSTRACT: Background: Reactive balance training (RBT) has been previously found to reduce fall risk in individuals with sub-acute stroke; however, our understanding of the effects of RBT on specific balance impairments is lacking. Objective: To quantify changes in common balance reaction impairments in individuals with sub-acute stroke resulting from RBT, relative to traditional balance training, using a prospective cohort study design with a historical control group. Methods: Individuals with sub-acute stroke completed either RBT or traditional balance training as part of their routine care during physiotherapy in inpatient rehabilitation. Reactive balance control was assessed using lean-and-release perturbations pre-intervention, post-intervention, and 6-months post-intervention (follow-up). Individuals with impaired balance reactions (delayed foot-off times, slide steps, and/or a preference for stepping with the preferred limb) at the pre-intervention assessment were identified using video and force plate data. Outcome measures (foot-off times, frequency of trials with slide steps, and stepping with the preferred limb) from the RBT participants with impaired reactions were compared for each of the three assessments to the mean values for the participants with impaired reactions in the historical control group. Results: Improvements were observed in all outcome measures for the RBT participants between pre-intervention and post-intervention, and/or between post-intervention and follow-up. These improvements were generally equivalent to, if not better than, the improvements demonstrated by the historical control group. Conclusions: Findings further support the use of RBT for post-stroke inpatient rehabilitation, and provide insight into specific balance reaction impairments that are improved by RBT.